Análisis técnico y económico sobre implementación de encofrados plásticos reutilizables en losas de hormigón armado en edificaciones altas - Brito Pinzón, Juan Daniel (2025)
This research analyzes the technical and economic feasibility of using reusable plastic formwork in reinforced concrete slabs for high-rise buildings, compared to traditional wood and metal systems. The main objective was to determine whether this innovation represents an efficient alternative in terms of cost, execution time, and sustainability. The methodology involved the preparation of unit prices, construction schedules, and evaluation of the reuse cycles of each system. A representative case of a 10-story building with a slab area of 2,000 m² was analyzed, calculating the costs and performance of each type of formwork. The results show that wooden formwork allows a maximum of 19 reuses, while metallic systems reach up to 150. In contrast, plastic formwork withstands up to 100 cycles while maintaining rigidity and surface quality. Economically, the initial cost per m² of plastic formwork is 25% higher than that of wood; however, when considering its service life, the total expenditure is reduced by 35% compared to metallic formwork and by 50% compared to wood. Additionally, execution times decrease by 20% due to the lightweight nature and ease of assembly of the plastic system. It is concluded that plastic formwork constitutes a viable and sustainable alternative, providing constructive efficiency and significant cost reduction in high-rise buildings.